(untitled) (Research, Society and Development, 2021)
Objective: to investigate the most frequent radiological findings in the international literature in the respiratory system of patients infected with Sars-CoV-2. Methodology: This is a Systematic Literature Review (RSL), a search being performed in the Pubmed and Cochrane Library databases, using a comprehensive search for the following terms and their correlates based on the Medical Subject Headings (MeSH): Coronavirus Infection, Respiratory Systems, Imaging, Diagnostic. Observational studies published from 2020 in any language were included. Results: After screening, 8 studies were included, with a total population of 1,089 patients from 6 different countries. Discussion: patients infected by Sars-CoV-2 were obtained by two categories of imaging tests: Computed Tomography and Pulmonary Ultrasonography, and pulmonary involvement is closely related to the severity and presence of risk factors. Conclusion: the results show the importance of radiological findings as a complementary tool in the diagnosis and prognosis of COVID-19, although they should not replace laboratory tests in confirming the diagnosis.